Restorative Justice vs. Retribution: Combating Online Radicalization and Recidivism in Juvenile Terrorism Offenders - Riani Widyaswara; Riswadi (Journal of Legal and Cultural Analytics, 2026)
Juvenile delinquency has evolved in the digital age, with increasing online radicalization among young people creating challenges for traditional criminal justice systems. The rise in terrorism-related offenses by minors in Southeast Asia and Europe, often fueled by extremist content on social media, highlights the need to assess whether restorative justice provides better rehabilitation and lower recidivism than punitive approaches. Using a mixed-methods design, this study analyzed 120 juvenile court cases from Indonesia and the UK (2018–2025), conducted interviews with 45 legal practitioners and psychologists, and applied thematic analysis and logistic regression. Findings show that restorative justice reduced recidivism by 62%, compared with 28% under punitive measures, with family mediation and AI-based early detection emerging as key factors. However, implementation challenges remained in low-resource settings. The study recommends a hybrid international framework grounded in the UN Convention on the Rights of the Child and supported by ethical digital monitoring to strengthen rehabilitative juvenile justice outcomes.